Xanthoceras sorbifolium Bunge: A Review on Botany, Phytochemistry, Pharmacology, and Applications - Zang, Erhuan; Qiu, Bin; Chen, Namuhan; Li, Caifeng; Liu, Qian; Zhang, Min; Liu, Yuchao; Li, Minhui (Frontiers in Pharmacology, 2021)
Xanthoceras sorbifolium Bunge (Sapindaceae) is a native Chinese plant with promising applications as a biofuel feedstock and a source of novel drugs. Historical records and documents from different periods have mentioned the use of X. sorbifolium and its botanical constituents in treating diseases, highlighting its central role in Chinese and Mongolian traditional medicinal therapies. Phytochemical research has focused on the husks, leaves, trunks, and branches of this herb. A total of 278 chemical compounds have been isolated and divided into 8 categories: triterpenoids, flavonoids, phenylpropanoids, steroids, phenols, fatty acids, alkaloids, and quinones. Modern pharmacological studies on X. sorbifolium have demonstrated positive effects on learning and memory, as well as anti-inflammatory, anti-tumor, and anti-oxidative properties. This review provides a comprehensive analysis of the available research on X. sorbifolium, focusing on the relationship between chemical constituents, traditional uses, and pharmacological effects. We also assess the potential for therapeutic and other applications of this plant in support of further research and development of X. sorbifolium.